Case Report: Looks can deceive: acute postoperative progressive renal dysfunction and hyperkalemia without significant hydronephrosis - Lahiji, Reza; Yildirim, Ahmet; Luke, William; Storino Ramacciotti, Lorenzo; Morton, Ernest A.; Helman, Talia Avigail; Nguyen, Jocelyn; Grajales, Valentina; Joshi, Shreyas S.; Narayan, Vikram M.; Nabavizadeh, Behnam; Hajiha, Mohammad; et al. (Frontiers in Oncology, 2026)
IntroductionHydronephrosis is typically considered a hallmark radiographic finding of urinary tract obstruction, expected to develop within 7 days of onset. However, this timeline may not apply universally. We report a rare case of delayed-onset hydronephrosis in the context of borderline end-stage renal dysfunction following radical nephrectomy in a patient with metastatic renal cell carcinoma (RCC), emphasizing the limitations of imaging in the early diagnosis of obstruction.Case presentationA 59-year-old male patient with metastatic renal cell carcinoma underwent right cytoreductive nephrectomy for an 8.5-cm renal mass with significant retroperitoneal lymphadenopathy and pulmonary metastases. Preoperative imaging showed mild left-sided hydronephrosis, and baseline renal function was preserved [estimated glomerular filtration rate (eGFR) 68 mL/min/1.73 m2]. Postoperatively, the patient immediately began experiencing a rapidly progressive decline in renal function, with eGFR falling to 15 mL/min/1.73 m2 and serum potassium rising to 7.0 mmol/L. Repeat imaging performed 8 days following initial decline was unremarkable, with findings consistent with prior scans. Subsequent nuclear medicine studies confirmed delayed perfusion and obstructive physiology in the solitary kidney. A nephrostomy tube was placed 15 days following the decline, leading to rapid improvement in renal function (eGFR 44 mL/min/1.73 m2 by POD 41).DiscussionThis case illustrates the potential for clinically significant obstruction to occur in the absence of early hydronephrotic changes on imaging. We hypothesize that hyperacute progressive obstruction may lead to rapid intrarenal pressure stabilization, limiting capsular stretch and delaying radiographic findings. The absence of pain and significant radiographic hydronephrosis contributed to diagnostic delay.ConclusionsThe absence of hydronephrosis on imaging cannot exclude obstruction, particularly in patients with a solitary functional kidney and high-risk features such as retroperitoneal malignancy. Early clinical deterioration should prompt a high index of suspicion and further diagnostic evaluation to prevent irreversible renal injury.